Extent of Ischemic Brain Injury After Thrombotic Stroke Is Independent of the NLRP3 (NACHT, LRR and PYD Domains-Containing Protein 3) Inflammasome. Issue 5 (May 2019) - Lemarchand, Eloise; Barrington, Jack; Chenery, Alistair; Haley, Michael; Coutts, Graham; Allen, Judith E.; Allan, Stuart M.; Brough, David
Abstract : Background and Purpose—: A major process contributing to cell death in the ischemic brain is inflammation. Inflammasomes are multimolecular protein complexes that drive inflammation through activation of proinflammatory cytokines, such as IL (interleukin)-1β. Preclinical evidence suggests that IL-1β contributes to a worsening of ischemic brain injury. Methods—: Using a mouse middle cerebral artery thrombosis model, we examined the inflammatory response after stroke and the contribution of the NLRP3 (NACHT, LRR and PYD domains-containing protein 3) inflammasome to ischemic injury. Results—: There was a marked inflammatory response after stroke characterized by increased expression of proinflammatory cytokines and NLRP3 and by recruitment of leukocytes to the injured tissue. Targeting NLRP3 with the inhibitor MCC950, or using mice in which NLRP3 was knocked out, had no effect on the extent of injury caused by stroke. Conclusions—: These data suggest that the NLRP3 pathway does not contribute to the inflammation exacerbating ischemic brain damage, contradicting several recent reports to the contrary. Abstract : Supplemental Digital Content is available in the text.